Endogenous gamma interferon mediates resistance to Brucella abortus infection. - Zhan, Y (1993)
Depletion of endogenous gamma interferon (IFN-gamma) with anti-IFN-gamma monoclonal antibody resulted in increased numbers of Brucella abortus in the spleen and liver of infected CBA mice. This increase was accompanied by a decrease in splenomegaly and a lower proportion of macrophages in the spleen. Furthermore, treatment of recipient mice with anti-IFN-gamma antibody blocked the adoptive transfer of resistance with immune T cells. Together, the results indicated that endogenous IFN-gamma plays an important role in mediating resistance to primary and secondary Brucella infection.